Incident light management in a thin silicon solar cell using a two-dimensional grating according a Gaussian distribution. (1st September 2019) - Heidarzadeh, Hamid
Highlights: The effect of non-uniformity of the rectangle gratings sizes to manage the light. Increasing the optical path length of incoming light in a thin silicon solar cell. A comprehensive study of the effect of angle of incident light. The efficiency for incidence angles between of 5° and 20° is better than the normal incident. Abstract: The main purpose of this work is to investigate the efficiency dependence of a thin silicon solar cell on non-uniformity in size of the rectangle back gratings. Here, efficiency enhancement is done using a rectangular back grating with a Gaussian random distribution. The grating is one of the main optical trapping strategies. A rectangle grating is placed at the rear as a mirror that reflects and scatters light into absorber to increase the light traveling length inside the active region. DBR and horizontal grating is used in the rear side and we focus on non-uniformity of rectangle grating sizes to govern the light inside the cell. The results show using this structure, we can manage the absorption spectra and the photocurrent significantly is increased. The efficiency of a 3 µm Si-type solar cell is increased near to 20%. In addition, when the angle of incidence is considered between 5–20°, the efficiency of the proposed structure is higher than the normal incidence. It is believed that the obtained results are helpful in the design of a thin film silicon solar cell.